Kajian Terapan Eko-Interior pada Bangunan Berwawasan Lingkungan Rumah Dr. Heinz Frick di Semarang; Kantor PPLH di Mojokerto; Perkantoran Graha Wonokoyo di Surabaya - Yusita Kusumarini; Agus Sachari; Budi Isdianto (Journal of Visual Art and Design, 2007)
The intertwined influence of both local and global phenomena toward the disturbance of environment requires immediate awareness of all; including also designers, architects, and building contractors. Yet, it is hardly to find concrete application in the field of interior design that embeds ecological approach on buildings, especially for the case of Indonesia. To address the issue, this study looks into several buildings in Java that have applied ecological-approach, a balanced-way between human, space, and environment. Having the purpose to investigate and to compare applied ecological-approaches of each building, the results are aimed to provide applicable-examples and/or a referential model for ecological building in Indonesia. Henry HCM Christiaans's cyclical-applied research was adopted as a method for the study, which consists of practical problem, diagnosis, plan, intervention, and evaluation. The compared results of each selected building and their examples of environmental approach are presented and discussed.